PENGEMBANGAN USER INTERFACE (UI) WEBSITE PT.SAAMPARAN DIGITAL GRUP DENGAN METODE KANSEI ENGINEERING (STUDI KASUS : PT.SAAMPARAN DIGITAL GRUP) - Dzikwan Firdaus, Alif; Yudi Permana, Nana; Sidiq, Maulana (Jurnal Mahasiswa Sistem Informasi Galuh, 2025)
The development of website technology makes it easier for developers to design products that meet user needs. This study aims to produce a User Interface (UI) design using Kansei Engineering Type I to create a website aligned with users’ preferences. The research process involved determining Kansei words, preparing a Semantic Differential scale, collecting specimens, and classifying design elements. Data analysis applied Coefficient Correlation Analysis (CCA), Principal Component Analysis (PCA), and Factor Analysis (FA). The results were translated into design elements using Partial Least Square (PLS).